Pemanfaatan Media Sosial dan Pengaruhnya terhadap Prestasi Belajar PAI di SMA Kabupaten Pidie Jaya - Mulyana, Mulyana; Salami, Salami; Nurbayani, Nurbayani (Tadabbur: Jurnal Peradaban Islam, 2024)
Education is defined as an effort undertaken by a person or group of people to become mature or reach a higher level of life or livelihood in a mental sense. Islamic education in the general sense is "education based on al-Islam", or often also referred to as education based on the Qur'an and the Sunnah of the Prophet. The function of Islamic education is to provide all facilities that can enable the tasks of Islamic education to be achieved and run smoothly. The aims of this research are: 1) To determine the use of social media of students at SMAN 1 Panjang Buya and SMAN 2 Bandar Dua in Pidie Jaya Regency. 2) To determine the PAI learning achievement of students at SMAN 1 Panjang Buya and SMAN 2 Bandar Dua in Pidie Jaya Regency. 3) To find out how much influence the use of social media has on PAI Learning Achievement at SMAN 1 Panjang Buya and SMAN 2 Bandar Dua in Pidie Jaya Regency. The method used in this research is Mix Method, which is a combination of qualitative and quantitative research methods. The population is the entire research object, in this case all religious teachers and students at Pidie Jaya Regency High School. By using purposive sampling, namely selecting members of a certain population to be used as samples, especially religious teachers. Then, to complete the data from respondents, sources were determined deliberately with the consideration that they could explain the use of social media as a PAI learning medium in Pidie Jaya Regency High School. This research has a weakness, in that it does not cover all high schools in Pidie Jaya Regency. Therefore, further research is needed to perfect it. The research results showed that students at SMA Negeri 2 Bandar Dua and SMA Negeri 1 Panjang Buya predominantly used social media for online business as much as 43%, apart from that students also dominantly used social media as a learning medium compared to non-learning. And PAI learning achievement is that the two high schools, both SMAN 1 Panjang Buya and SMAN 2 Bandar Dua, achieved PAI learning achievement with an average score of 78. The difference is not very significant. SMAN 1 Panjang Buya got an average score of 78.54 while SMAN 2 Bandar Dua got an average score of 78.73. So the difference in scores between the two schools, SMAN 1 Panjang Buya and SMAN 2 Bandar Dua is only around 0.14. As well as descriptive analysis that has been carried out on the use of social media by students of SMA Negeri 2 Bandar Dua and SMA Negeri 1 Panjang Buya. The F statistical value was obtained at 0.796 with a p-value of 0.379. The P-value (0.379) is greater than the significance level (0.05), so it can be concluded that there is no influence of X (social media use) on students' PAI scores (Y).